Digital Inclusion for People with Autism Spectrum Disorders: Review of the Current Legal Models and Doctrinal Concepts - J. Hutson; P. Hutson (Journal of Digital Technologies and Law, 2023)
Objective: today, a significant part of professional tasks are performed in the digital environment, on digital platforms, in virtual and other meetings. This necessitates a critical reflection of traditional views on the problem of accessible environment and digital accessibility, taking into account the basic universal needs of persons with disabilities.Methods: a gap between the traditional legal perspective on special working conditions for persons with disabilities and the urgent need of a digital workplace (digital environment) clearly shows lacunas in the understanding of accessibility, which are identified and explored with formal-legal and doctrinal methods. The multifaceted aspects of digital inclusion are revealed based on an informative approach to legislation. It leads, among other things, to searching for recommendations which would fill this gap and contribute to the creation of a more inclusive and responsible legal, social and technological environment.Results: the research has led to a conclusion that the existing legal, social and technological paradigms need to be re-evaluated. This reevaluation should aim to develop a more inclusive and benevolent concept of accessible environment that takes into account the diversity of human experience and needs, and a wide range of behavioral and cognitive characteristics. Creating special conditions in the workplace for those with overt and covert health problems should become an integral part of the employer's focus, along with improving management efficiency.Scientific novelty: covert (hidden) health problems have traditionally been understudied, although they include a range of mental and physical impairments, which, like explicit health problems, vary in their origin, intensity, and permanent or episodic character. This study fills a gap in the issues of disability and its legal protection, taking into account the trend of digital inclusion, the dynamic labor activity of today, and the wide range of human abilities and needs.Practical significance: the aspects of hidden or latent disability considered in the study provide a different perspective at employment, focusing on the workplace conditions that could be created. Employers may be unaware of the need to create special working conditions for those with hidden health problems. This results in negative effects on unemployment, increased sick leave, limited opportunities in the workplace, and more. Employees are often reluctant to disclose their non-obvious health problems to employers; hence, employers should facilitate disclosure of such information by creating relevant conditions. Such an approach will contribute to the legal protection of this category of employees and to further development of the existing legislative regulation, since the latter does not fully comply with today's needs and changed reality.